Dialog, etyka, gospodarka. Zastosowania dialogu w zarządzaniu w ujęciu niemieckojęzycznej etyki gospodarczej - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2012)
The article presents the conditions to be met by the conversation to become a dialogue. Based on the concept of dialogue wasestablished philosophy and ethics of dialogue, which we present. Its representatives include: Jurgen Habermas and Karl Otto Apel. Then,on the example of German business ethics demonstrates how philosophy and ethics of dialogue could become the foundationof the Republican economic ethics created by Peter Ulrich and business ethics developed by Horst Steimann. In the opinion of the author,they may be helpful in developing a new version of business ethics, which is formed under the influence of reflection on experiencesFinancial and economic crisis that began in 2008, and whose effects are visible to this day.